An assessment of routine primary care health information system data quality in Sofala Province, Mozambique - Cuembelo Fatima; Karagianis Marina; Lara Joseph; Lambdin Barrot; Micek Mark; Gimbel Sarah; Gloyd Stephen S; Pfeiffer James; Sherr Kenneth (BMC, 2011)
Abstract Background Primary health care is recognized as a main driver of equitable health service delivery. For it to function optimally, routine health information systems (HIS) are necessary to ensure adequate provision of health care and the development of appropriate health policies. Concerns about the quality of routine administrative data have undermined their use in resource-limited settings. This evaluation was designed to describe the availability, reliability, and validity of a sample of primary health care HIS data from nine health facilities across three districts in Sofala Province, Mozambique. HIS data were also compared with results from large community-based surveys. Methodology We used a methodology similar to the Global Fund to Fight AIDS, Tuberculosis and Malaria data verification bottom-up audit to assess primary health care HIS data availability and reliability. The quality of HIS data was validated by comparing three key indicators (antenatal care, institutional birth, and third diptheria, pertussis, and tetanus [DPT] immunization) with population-level surveys over time. Results and discussion The data concordance from facility clinical registries to monthly facility reports on five key indicators--the number of first antenatal care visits, institutional births, third DPT immunization, HIV testing, and outpatient consults--was good (80%). When two sites were excluded from the analysis, the concordance was markedly better (92%). Of monthly facility reports for immunization and maternity services, 98% were available in paper form at district health departments and 98% of immunization and maternity services monthly facility reports matched the Ministry of Health electronic database. Population-level health survey and HIS data were strongly correlated (R = 0.73), for institutional birth, first antenatal care visit, and third DPT immunization. Conclusions Our results suggest that in this setting, HIS data are both reliable and consistent, supporting their use in primary health care program monitoring and evaluation. Simple, rapid tools can be used to evaluate routine data and facilitate the rapid identification of problem areas.